REKONSTRUKSI PERAN DAN FUNGSI MASJID SEBAGAI PUSAT KEGIATAN PENDIDIKAN ISLAM - Mulyono Mulyono (Universitas Muhammadiyah Ponorogo, 2017)
Rasulullah SAW has given the role in the effort to create the ability of Muslims to become kholifah on earth and devoted servant of Allah SWT by doing Islamic education to the companions in the mosque. This tradition is followed by the followers of Islam and the subsequent Islamic rulers, even in the development of Islamic scholars the process of